Child rights imperatives for children in alternative care - Hiranthi Wijemanne (Scottish Journal of Residential Child Care)
The paper identifies human rights issues related to all children in alternative care institutions, causal factors and how these need to be addressed, and the prevention of the risks of neglect and abuse. Attention is drawn to the state's responsibilities related to supporting vulnerable families of such children; this includes community-based preventive approaches, including the promotion of better parenting practices. Emphasis is placed on childhood disabilities and other factors which contribute to institutionalisation and its impact on the well-being of children. Estimated numbers of affected children in South Asia are referred to in the context of recognising the extent of the problem and the huge challenges to reach out to all the affected children with quality services. Emphasis is placed on the need for the resolution of such issues in the context of childhood vulnerabilities. The special issues of disabled children and adoption processes are referred to. Attention is drawn to the state's responsibilities as signatories to the Convention on the Rights of the Child, and their obligations to establish and ensure the implementation of rights-based standards for quality care and protection, the importance of independent monitoring of the care being provided and the need to emphasise child protection in all instances. The necessity to plan for all children when they leave the institution is emphasised.